Evaluation of canine bone marrow-derived mesenchymal stem cells for experimental full-thickness cutaneous wounds in a diabetic rat model. (2nd December 2021) - Bist, Deepika; Pawde, A. M.; Amarpal,; Kinjavdekar, Prakash; Mukherjee, Reena; Singh, K. P.; Verma, Med Ram; Sharun, Khan; Kumar, Amit; Dubey, Pawan K.; Mohan, Divya; Verma, Amit; et al.
ABSTRACT: Background: The wound healing potential of canine bone marrow-derived mesenchymal stem cells (BMSCs) was evaluated in the excisional wound of streptozotocin-induced diabetic rats. Research design and methods: Xenogenic BMSCs were collected aseptically from the iliac crest of healthy canine donors under general anesthesia. Full-thickness experimental wounds (20 × 20 mm 2 ) on the dorsum of forty-eight adult healthy Wistar white rats. The wounds were assigned randomly to three treatment groups: PBS (Group A) or BMSCs (Group B) injected into the wound margins on days 0, 7, and 14 or BMSCs (Group C) injected into the wound margins on days 7, 14, and 21 post-wounding. The degree of wound healing was evaluated based on macroscopical, hemato-biochemical, histopathological, and histochemical parameters. Results: The results indicated granulation tissue formation with reduced exudation and peripheral swelling in the treatment groups compared to the control group A. Similarly, the degree of wound contraction was significantly higher in groups B and C animals than group A on days 14 and 21 post-wounding. The transplantation of BMSCs resulted in early drying of wounds, granulation tissue appearance, and enhanced cosmetic appearance. Conclusion: The histopathological, histochemical, and gross findings suggested the therapeutic potential of xenogeneic mesenchymal stem cell therapy in managing diabetic wounds. Abbreviations: BMSCs-bone marrow-derived mesenchymal stem cells, PBS-phosphate-buffered saline, MSCs-mesenchymal stem cells, FBS-fetal bovine serum, ECM-extracellular matrix